The recovery and retraction of memories of abuse: a scoping review - Otgaar, Henry; Mangiulli, Ivan; Li, Chunlin; Jelicic, Marko; Muris, Peter (Frontiers in Psychology, 2025)
People who claim to have been abused sometimes retract these claims at a later point in time. Research on these so-called ‘retractors’ might provide critical insights into the processes involved in the recovery and retraction of traumatic memories. However, the literature on this topic is highly diverse in terms of, for example, methodology. Hence, the aim of the current scoping review was to amass the available literature on retractors and identify key themes. We identified 17 articles on the topic of retractors ranging from empirical studies to critical commentaries. A central theme that arose from the literature was the influence of therapy in the recovery of potentially false memories. That is, retractors noted that therapists frequently believed that they harboured unconscious repressed memories of abuse which had to be recovered during therapy. Furthermore, retractors repudiated their claims of abuse for various reasons such as physical evidence implying that their memory was false. Also, retraction took longer that the initial recovery of memories of abuse. Finally, after recantation, retractors’ memories varied considerably in terms of belief and recollection of the traumatic event with some accounts qualifying as nonbelieved memories. This review offers critical knowledge of a rather understudied population providing further insight in how traumatic events can sometimes be misremembered.